9x-2(3x-2)=5(x-2)

Simple and best practice solution for 9x-2(3x-2)=5(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-2(3x-2)=5(x-2) equation:



9x-2(3x-2)=5(x-2)
We move all terms to the left:
9x-2(3x-2)-(5(x-2))=0
We multiply parentheses
9x-6x-(5(x-2))+4=0
We calculate terms in parentheses: -(5(x-2)), so:
5(x-2)
We multiply parentheses
5x-10
Back to the equation:
-(5x-10)
We add all the numbers together, and all the variables
3x-(5x-10)+4=0
We get rid of parentheses
3x-5x+10+4=0
We add all the numbers together, and all the variables
-2x+14=0
We move all terms containing x to the left, all other terms to the right
-2x=-14
x=-14/-2
x=+7

See similar equations:

| 1/10y-5=-19 | | -2=4/5x=6 | | 7-x÷8=6 | | 26x+43=5(8x+3) | | 12d-4=-7 | | -4x+5=-4x-4−4x+5=−4x−4 | | z÷10-1=5 | | x=90-(4x+12) | | n/4=12n= | | 4(v-1)=-9v-30 | | x=90-(4+12) | | 5(v+8)-8v=28 | | v/2-15=21 | | 3y-2=6(y-1)-3y | | 69.6=6(m+3.2 | | 8n=-40n= | | 14=-8u+2(u-8) | | 6x−6=15x+15 | | 105.3=9(m+2.9) | | -1z+5=7 | | 4x/2+10/5=20 | | 20w+100=400 | | 15=x/3=8 | | 72=6(m+3.7) | | −75x+57=−75x+57 | | -24=-6p/7 | | 10+200+10x=1000-69x | | 4n-7=5n | | 5−6(x+4)=15 | | 1768=34(p+10) | | 2x2-22=50;6 | | 1/6(6x-18)=-3 |

Equations solver categories